The Ability of Primer IS900 and F57 to Detect Mycobacterium avium subspecies paratuberculosis by Conventional PCR - Widagdo Sri Nugroho, WSN; Mirnawati Sudarwanto, MS; Denny Widaya Lukman, DWL; Surachmi Setyaningsih, SS; Abdulwahed Ahmed Hassan, AAH; Ewald Usleber, EU (Universitas Putra Malaysia, 2009)
Johne's disease (JD) is chronic granulomatous enteritis in ruminants which infected by Mycobacterium avium subspecies paratuberculosis (MAP) and this inflammatory disorder shows many similarities to Crohn's disease (CD) in human. Few researches conducted in Europe, USA, and Australia showed the relationship among MAP, CD, JD and dairy products. The detection method of MAP was developed by using polymerase chain reaction (PCR). The most popular primer used in this method was IS 900 but in the last few years, some researchers developed primer F57 to improve its accuracy. Some researchers showed that a variety of performance of both primers on the MAP depends on the samples and the amount of bacteria in it. The aims of this study were to evaluate sensitivity and specificity of the primer IS 900 and F57 to detect MAP by conventional PCR. Primers configurations of IS900 described by Bull (2003) are (TJ1: 5'-GCT GAT CGC CTT GCT CAT-3' and TJ2: 5'-CGG GAG TTT GGT AGC CAG TA-3'). And oligonucloetide of primer F57 are F57/R57(F57:5'-CCT GTC TAA TTC GAT CAC GGA CTA GA-3' and R57:5'-TCA GCT ATT GGT GTA CCG AAT GT-3') (Vansnick et al. 2004). Sensitivity test was done by using serial dilutions of MAP reference from 100-106 cell/ml in PBS Tween 0.5%. Every dilution suspension of MAP was inoculated into herrold's egg yolk medium enrichment with mycobactin J as a gold standard. Specificity evaluation was done by comparing the MAP to Mycobacterium avium subspecies avium (MAV), Escherichia coli, Listeria ivanovii, Pseudomonas aeruginusa, Streptococcus agalactiae, Klebsiella pneumoniae, Staphylococcus hyicus, Streptococcus infatis, and Listeria monocytogenes. The result showed that both primers specific for MAP DNA. The primer IS 900 detected MAP DNA from 104 cell/ml and primer F57 detected at 103 cell/ml.